PENGARUH PENGGUNAAN MEDIA SOSIAL BAGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Mardinawati Mardinawati; Budhi Adhiani; Sumanto Sumanto; Teguh Budi Santosa; Maharani Rona Makom (Politeknik Negeri Semarang, 2023)
The research was conducted on Micro, Small and Medium Enterprises (MSMEs) in the Magelang and Temanggung areas. The problem in this study is whether social media and its benefits affect the development of Micro, Small and Medium Enterprises (MSMEs). How does the use of social media affect the marketing of Micro, Small and Medium Enterprises (MSMEs). The purpose of this study is to determine the effect of using social media on the development of Micro, Small and Medium Enterprises (MSMEs). to determine the effect of using social media on the marketing of Micro, Small and Medium Enterprises (MSMEs). The method in this research is this research is a descriptive observational research on Micro, Small and Medium Enterprises (MSMEs) in Magelang City and Temanggung City. This study uses in-depth interviews and observations of SMEs. Methods of descriptive statistical analysis and qualitative analysis. Results are displayed in tables and graphs. The results show that MSMEs have used social media in developing their business, especially in product introduction and marketing. The most widely used social media are Facebook, Instagram and WhatsApp